2017
DOI: 10.1007/s10590-016-9184-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel and robust approach for pro-drop language translation

Abstract: A significant challenge for machine translation (MT) is the phenomena of dropped pronouns (DPs), where certain classes of pronouns are frequently dropped in the source language but should be retained in the target language. In response to this common problem, we propose a semi-supervised approach with a universal framework to recall missing pronouns in translation. Firstly, we build training data for DP generation in which the DPs are automatically labelled according to the alignment information from a paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This is particularly relevant because one potential explanation for the absence of a significant association between subjective FPSPs and suicidal ideation could be the phenomenon of pro-drop in Chinese. Pro-drop is observed in languages such as Chinese and Japanese, where the subject of a sentence can be dropped without affecting the sentence鈥檚 meaning or grammatical structure [ 36 ]. Given that the data analyzed in this study consist of Chinese text, it is highly likely that the prevalence of pro-drop reduced the occurrence of subjective FPSPs, making it challenging to observe a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant because one potential explanation for the absence of a significant association between subjective FPSPs and suicidal ideation could be the phenomenon of pro-drop in Chinese. Pro-drop is observed in languages such as Chinese and Japanese, where the subject of a sentence can be dropped without affecting the sentence鈥檚 meaning or grammatical structure [ 36 ]. Given that the data analyzed in this study consist of Chinese text, it is highly likely that the prevalence of pro-drop reduced the occurrence of subjective FPSPs, making it challenging to observe a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Spoken Chinese Contains More Pro-drop Than Literary Language Formally, pro-drop refers to a reference position that is filled with amorphologically unrealized form, and is one of the most common referential options in many languages such as Chinese (Wang et al, 2018a), Japanese (Taira et al, 2012), Korean (Park et al, 2015), and Thai (Kawtrakul et al, 2002). Previous studies have revealed that spoken Chinese language tends to contain more pro-drops than literary language (Wang et al, 2016(Wang et al, , 2017Xu et al, 2021). However, quantitative studies on pro-drops in different genres of spoken Chinese, remain scarce.…”
Section: Pronoun-dropping Analysismentioning
confidence: 99%
“…In particular, it results in the omission of the subject pronoun. As pointed out by recent studies, this misalignment produces difficulties in the translation process since the missing pronoun is challenging to be reproduced, and it affects the order of dependencies in the sentence [50,51]. For that reason, from a practical point of view, the refinement rules for the target language have been focused on improving the use of personal and possessive pronouns and, in addition, of possessive and demonstrative adjectives.…”
Section: Linguistic Refinementmentioning
confidence: 99%